Evaluation of retinal fibre layer thickness and optic nerve head parameters in obstructive sleep apnoea patients - Halim, Nazihatul Fikriah Abd (2017)
Introduction Obstructive sleep apnea (OSA) is a sleep-related breathing disorder which can be life threatening characterized by partial (hypopnoeas) and complete pauses (apnoeas) in breathing lasting at least 10 seconds during sleep. As a result, the blood oxygen saturation may fall, with resulting in a hypoxia state. OSA has been associated with ocular conditions such as non-arteritic anterior ischemic optic neuropathy (NAION), papilloedema, glaucoma and central retinal vein occlusion. Optical Coherent Tomography (OCT) can measure the retinal nerve fibre layer (RNFL) thickness and optic nerve head (ONH) parameter changes that can result from the disease. Objective The aim of this study was to compare the changes of RNFL thickness and ONH parameters in patients with OSA and control group. We also analyzed the relationship between these parameters with the severity of OSA. Material and methods A comparative cross-sectional study was conducted in Hospital Universiti Sains Malaysia involving 54 samples who was diagnosed to have OSA based on overnight polysomnography (PSG) and 54 control subjects. A complete ocular examination was performed. RNFL thickness and ONH parameters were measure using the OCT. Independent t-test, chi square, Exact Fisher test, correlation and regression analysiswere use in the statistical analysis. Results There were statistically significant thinning of the RNFL of the OSA group compared to control. In obstructive sleep apnoea group (OSA), mean of average RNFL thickness was 93.87μm, SD= 9.17, p=0.0008 (p<0.05) while superior RNFL thickness was 113.59μm, SD=16.29, p= <0.001 (<0.05). The changes in RNFL thickness has fair significant linear relationship with the severity of the disease particularly involving superior RNFL with R=0.293, R2= 0.087 r= -0.293 p=0.030 (p<0.05), and nasal RNFL R=0.292, R2=0.085, r= -0.292 p=0.032 (p<0.05). Optic nerve head parameters had no significant difference from control and there was no significant direct linear relationship of all the optic nerve head parameters with the severity of the disease. However, the RNFL thickness was confounded by dyslipidaemia. Conclusion OSA patients have significantly thinner in average and superior RNFL layer compared to control. There was fair significant direct linear relationship of RNFL thickness with the severity of the disease.